Input Problems in SMEs: Policy Issues and Challenges - Shrestha, Ramesh (PYC Nepal Journal of Management, 2011)
The paper attempts to examine the input problems in SMEs and the policy issues and challenges thereof. SMEs in Nepal use both indigenous and imported raw materials for the production of output. Due to problems of unavailability, ambiguous and unfavourable public policies, involvement of agents and importers, higher prices of raw materials, many SMEs have been closed down and some are on the verge of closing, leaving many people unemployed. Therefore, conscious efforts must be made by all quarters to overcoming the problems, and at the same time the government should provide tax concessions and other incentives to those SMEs which particularly use local raw materials.